(untitled) (EU and comparative law issues and challenges series (ECLIC), 2020)
As the main tool for the achievement of the proper functioning of the internal market, the Union is focused on the process of harmonization. The role of harmonization in the EU’s internal market is to remove barriers to trade and to facilitate free movement of goods, persons, services, and capital (as well as payment). This can be achieved in many ways, including through the adoption of harmonization, i.e., approximation measures, such as directives and regulations. The established CJEU case law confirms that the aim of harmonization measures is to ‘reduce disparities between legal systems.’ This aim’s realization very often depends upon the form of the chosen harmonization measure and the level of harmonization the measure is based on (e.g., minimum, maximum, full (targeted) harmonization). However, today, we are faced with changes in the regulatory approach of the EU legislator and these changes are greatly affecting the process of harmonization. Due to the increased level of harmonization, EU directives are starting to appear and function more like EU regulations, and vice versa. Because of numerous optional clauses, clauses of minimal harmonization, and the so-called ‘opening clauses’, EU regulations are not reducing but enabling ‘disparities between legal systems.’ As an example, authors are analyzing the EU’s General Data Protection Regulation (GDPR) containing more than 69 opening clauses, which play an important role in the process of harmonization and present an instrument of interplay between EU law and Member States’ laws. Therefore, it remains to be answered within the lines of this paper whether the role of opening clauses is in compliance with the aim of harmonization in the EU law.